Minimization of a SynRel's oscillating torque by calculation of the appropriate skew angle. Issue 3 (2nd May 2017) - Martinez, Javier; Krischan, Klaus; Muetze, Annette
Abstract : Purpose: Synchronous Reluctance (SynRel) motors are known to suffer from excessive torque ripples. The classical way to avoid this drawback of the motor is skewing the slots. This paper aims to provide an analytic estimation of the best skew angle to minimize the ripples in such SynRel motors with tooth windings. The approach used in this paper consists of the minimization of the spectral components of the magnetic energy that cause these oscillation torques. The method was validated by means of a multi-slice finite element model (FEM). Design/methodology/approach: An analytic model, based on permeance theory, is derived to analyse the electromagnetic phenomena taking place inside of the motor. This model allows the identification of the causes underlying the torque ripple production. Based on this understanding, the most suitable skew angle can be determined. The analytic method, together with the best skew angle, is validated by means of an FEM of a SynRel machine. Findings: A method to determine the optimum skew angle for a SynRel machine is presented. It depends on the wave-number of the magnetic waves producing the torque ripple. It is twice the one typically chosen for induction machines. Practical/implications: The proposed approach allows improving on the design methodology for the production of smoothly running SynRel machines. Originality/value: The methodology utilized in this paper is based on the relationship between the mechanical torque and the magnetic energy stored in the motor (virtual work law). From this, the best skew angle to eliminate the magnetic energy causing torque ripple can be determined. It, therefore, proposes an effective alternative to the common use of inductance models to determine such angles.